Length of Latency with Preterm Premature Rupture of Membranes before 32 Weeks' Gestation - Peaceman, Alan M.; Lai, Yinglei; Rouse, Dwight J.; Spong, Catherine Y.; Mercer, Brian M.; Varner, Michael W.; Thorp, John M.; Ramin, Susan M.; Malone, Fergal D.; O'Sullivan, Mary J.; Hankins, Gary D.V.; for the National Institute of Child Health and Human Development Maternal-Fetal Medicine Units Network (American Journal of Perinatology, 2015)
Objective The objective of the article is to describe latency for patients with preterm premature membrane rupture (PPROM) between 240/7 and 316/7 weeks' gestation.Study Design Secondary analysis of data collected prospectively in a multicenter clinical trial of magnesium sulfate for cerebral palsy prevention. Women with PPROM and fewer than six contractions per hour at enrollment who were candidates for expectant management (n = 1,377) were included in this analysis. Length of latency was calculated in days by subtracting the time of delivery from the time of membrane rupture.Results At each week of gestation, median latency between 24 and 28 weeks was similar at approximately 9 days, but it was significantly shorter with PPROM at 29, 30, and 31 weeks (p < 0.001). In addition, the percentage of patients remaining undelivered at 7 days and 14 days was similar for PPROM between 24 and 28 weeks, but it decreased significantly after that. For each gestational age, the proportion of patients remaining pregnant declined in a fashion similar to an exponential pattern.Conclusion Median latency after PPROM is similar from 24 to 28 weeks' gestation, but it shortens with PPROM at and after 29 weeks.
Keywords: latency; premature rupture of membranes; preterm birth